Gateways or backdoors to development? Filtering mechanisms and territorial embeddedness in the Chilean copper GPN's urban system. (4th November 2020) - Atienza, Miguel; Arias‐Loyola, Martín; Phelps, Nicholas
Abstract: This paper analyses the role played by different urban nodes in the Chilean copper mining Global Production Network (GPN), and how filtering mechanisms act in favour of the capital city, limiting the territorial embeddedness of extractive industry in resource peripheries. In doing so, we make three contributions to the literature. First, in addition to observing gateway cities (those connecting the mining hinterlands to the global economy), we propose an intermediate category in urban hierarchies which we label the "backdoor city" (those that can perform one or more functions of a gateway city but lack chances for value capture and sustainable development outcomes). Second, we analyse the filtering mechanisms that work to the detriment of resources peripheries. Third, we analyse how these mechanisms reduce the territorial embeddedness of mining activity across the Chilean urban hierarchy. Our main results show that the capital city of Santiago stands out as the only gateway city in the country, and Antofagasta acts as a backdoor city for the Chilean resource peripheries where the extractive activity is weakly embedded, limiting their development opportunities.